Efeitos do exercício aeróbio de baixa intensidade e da melatonina nos músculos esquelético e cardíaco de camundongos mdx - Bonjorno, Reinaldo Carlos (Universidade Federal de São Carlos, 2023)
Duchenne Muscular Dystrophy (DMD), affecting 1 in every 5,000 live births, affects the X chromosome, responsible for the synthesis of the dystrophin protein that maintains the stability of the cell membrane, making it resistant to mechanical forces. It causes ruptures, necrosis, and increased serum levels of cytoplasmic enzymes, which activate proteases, stimulating the degeneration of muscle fibers. The diagnosis is made through clinical examinations such as: muscle biopsy, Creatine Kinase (CK), and DNA measurement. Due to recurrent injuries, satellite cells are constantly activated to carry out the tissue repair process. In this way, these cells end up entering an exhaustion process, reducing the “pool” of quiescent cells, and affecting the regenerative process. Physical exercise is an important and low-cost therapy that has been explored in the rehabilitation of patients with DMD. Studies show that a lack of physical activity can determine changes in the functionality of the muscular, cardiac, and respiratory systems. Experimental studies with mdx mice have shown that low-intensity physical exercise increases the expression of CS, muscle mass, and strength and improves tissue cytoarchitecture. In parallel to therapies through physical exercise, DMD is also targeted by drugs. The most common of these is cortisol, a drug that is capable of significantly reducing the degenerative process of muscle fibers, but, on the other hand, causes side effects. Currently, melatonin has become the focus of research in the process of muscle regeneration after injury. Melatonin has several functions in the body, in addition to antioxidant and anti-inflammatory actions. Aiming at antioxidant and anti-inflammatory power, studies have shown that patients with DMD have increased expression of anti-inflammatory cytokines and these same authors have found a significant reduction in muscle necrosis markers. Exogenous administration of melatonin has been shown to increase the number of satellite cells and improve the strength and tissue morphology of normal skeletal muscles after physical exercise. Objective: Our objective was to analyze the morphofunctional and biochemical characteristics of dystrophic, skeletal, and cardiac muscles, after treatment with melatonin associated with low-intensity physical exercise. Results: The handgrip test showed that low-intensity aerobic exercise associated with melatonin induced a significant increase in grip strength in mdxTRM animals compared to mdxTR. In the morphological analysis of skeletal and cardiac muscles, it was possible to observe an improvement in the tissue morphology of the animals that were treated with melatonin in relation to the groups that did not receive the i.p. application. of melatonin. Regarding satellite cells, we can observe that the groups that completed the 21 training sessions presented greater PAX7 content, with the mdxTR group being the one that presented greater content compared to all other groups. For myogenin, the mdx and mdxM groups showed higher CS content in the fusion and differentiation phase, when compared to the trained groups. Using the Western Blot technique, we obtained promising results regarding the expression of the utrophin protein in the heart muscle, even without statistical significance.” The procedures imposed separately showed an increase in utrophin content when compared to the mdx group. The association of exercise and melatonin proved to be more efficient in morphology and in increasing the expression of utrophin. Conclusion: Both low-intensity aerobic exercise and melatonin improved the morphology of the psoas and cardiac muscles and also skeletal muscle function and when combined, these morphofunctional characteristics were even more expressive.
Effects of low-intensity aerobic exercise and melatonin on skeletal and cardiac muscles of mdx mice
Keywords: Distrofia muscular de Duchenne; Camundongos mdx; Melatonina; Exercício aeróbico de baixa intensidade; Utrofina; Células satélites; Músculo esquelético; Músculo cardíaco; Duchenne muscular dystrophy; mdx mice; Melatonin; Low-intensity aerobic exercise; Utrophin; Satellite cells; Skeletal muscle; Cardiac muscle; CIENCIAS BIOLOGICAS::FISIOLOGIA